International Trade in the Context of Sustainable Economic Development of World Countries - Savchenko Maryna V.; Priymak Evgeniy O.; Havrysh Ivan V. (Bìznes Inform, 2023)
There are many mechanisms in the world that ensure the economic development of states. One of them is international trade, which plays an important role in supporting the economic development of individual countries, regions and the world as a whole. This article examines the role of international trade in economic development, its impact on national economies, and the consequences for countries that freely practice international trade. To ensure economic development, the importance of international trade is obvious, and therefore it needs support at the level of states and regions. The theoretical and methodological basis of the research is the work of domestic and foreign scientists. The results were obtained due to the application of a system of methods. In particular, the methods of grouping, classification and quantitative comparisons were used in the study of the commodity and geographical structure of world exports and imports. The methods of structural and economic-statistical analysis were used to assess the main results of international trade and determine their impact on the development of both individual countries and entire regions. The graphic method was used to visualize the results of the analysis of international trade during the specified periods. The article is devoted to a detailed study of the prospects of international trade as a means of strengthening progress in the country's achievement of sustainable development goals. The article examines the state of international trade, considers the dynamics of export-import operations during the specified period. The consequences of foreign trade both for individual states and the world as a whole are considered. International trade is a significant impetus for development, as a result of which the economy of a single country develops more actively. The study of trends in the field of international trade makes it possible to predict the directions of development of the world economy.